Global Approaches to Early Learning Research and Practice: An Introduction. Issue 158 (15th December 2017) - Pugh, Kenneth R.; McCardle, Peggy; Stutzman, Annie
Abstract: This chapter introduces the issue, highlighting the importance of early childhood development and learning.